Autobiographical memory of validating and invalidating consultations is associated with recall capacity for health information - Charlotte E. Lee; Hollie Birkinshaw; Matthew Garner; Tamar Pincus (PLoS ONE, 2026)
Managing chronic pain involves cognitive and emotional challenges that may affect treatment adherence. Patients’ ability to remember clinician advice is therefore important. Clinician behaviours may influence these processes. To investigate whether recounting autobiographical memories of perceived validating (vs. invalidating) healthcare experiences influences subsequent recall of health-related information in people living with chronic pain, 245 adults with chronic pain (≥3 months) were recruited online. Eligibility criteria included: age ≥ 18 years, fluent in English, no hearing difficulties or mental health conditions, and at least one healthcare visit in the previous two years. Participants were quasi-randomly assigned to describe either a validating or invalidating consultation they had previously experienced. Before and after this task, participants rated their pain intensity and pain-related fear. Participants then listened to 20 health messages and were later asked to recall them in an incidental memory test. The primary outcome was incidental recall of health messages, operationalised as the likelihood of recalling each of the 20 messages. Secondary outcomes included pain intensity and pain-related fear. Recall was analysed using a binomial generalized linear mixed-effects model accounting for individual differences (pain intensity, pain-related fear, immersion in the task, age, sex, and pain duration).Participants who described a validating consultation were more likely to recall health messages than those in the invalidating condition (19% higher odds of recalling each message, based on model estimates). The association was not mediated by change in pain-related fear. These findings indicate that remembering validating consultations might boost retention of health information, highlighting clinician-validation as a potential strategy to support cognitive functioning in people living with chronic pain.